Sliding Mode Control of Buck Converter - Nagulapati Kiran (Institute of Advanced Engineering and Science, 2014)
DC-DC converters are used to convert DC voltage from one level to other. These converters are drastically used in industry as well as in research. One of the main limitations of these converters is unregulated supply of voltage and current. To overcome these problems there are various control techniques. This paper presents two such methods. This paper compares dynamic performance of buck Converter using PID controller and Sliding mode controller. Simulation of PI and Sliding mode control of Buck Converter is carried out in MATLAB SIMULINK.